Moodle based LMS implementation in higher education sector in Kerala. Perspectives and suggestions on implementation - എച്ച്. കെ. ഡോ. സന്തോഷ് (IRAYAM, 2018)
In higher education, both in classroom education and in the evolving online education, a comprehensive and efficient system of infrastructure should be in place at the state level with precise planning and centralization. This paper discusses the relevance and potential of Moodle LMS implementation in the higher education sector